Dynamics of equatorial F region irregularities from spaced receiver scintillation observations - Bhattacharyya, A.; Basu, S.; Groves, K.M.; Valladares, C. E.; Sheehan, R. (My University, 2001)
Spaced receiver observations of amplitude scintillations on a 244 MHz signal, at an equatorial station, have been used to study random temporal changes associated with the scintillation-producing irregularities and the variability of their motion. The computed drift of the scintillation pattern shows the presence of velocity structures associated with equatorial bubbles in the early phase of their development. On magnetically quiet days, after 22:00 LT, the estimated drifts fall into a pattern which is close to that of the ambient plasma drift. There is considerable decorrelation between the two signals until 22:00 LT. The power spectra of the most highly correlated scintillations recorded by spaced receivers indicate that the associated irregularities are confined to a thin layer on the bottomside of the equatorial F region. This suggests that the convection pattern associated with bottomside irregularities is stable due to the dominance of ion-neutral collisions over ion inertia.
Keywords: Equatorial station; F region; Scintillation observations